2016
DOI: 10.1021/acssuschemeng.6b02302
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Coupling Approach to Cross-Conjugated Polymers from Vanillin-Based Monomers

Abstract: We describe the use of vanillin-based monomers as a renewable feedstock for the synthesis of cross-conjugated polymers. This transformation exploits a catechyl-substituted phosphonite mediated multicomponent polymerization to convert vanillin-derived diimines, commercial diacid chlorides, and simple alkynes or alkenes into conjugated pyrrole-based polymers. The flexibility of the multicomponent polymerization has allowed for the efficient formation of families of vanillin-derived fluorescent polymers with tuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“… 367 These vanillin-derived diimines were converted into conjugated pyrrole-based polymers by a transformation exploiting a catechyl-substituted phosphonite-mediated multicomponent polymerization with commercial diacid chlorides and simple alkynes or alkenes (route 15d). 368 Importantly, this study reported, for the first time, a cross-conjugated polymer composed of both components of lignocellulosic biomass by using vanillin and furan-based acid chlorides. Polyvanillin, which is a functionalized polymer using totally renewable resources can be simply synthesized by electrochemical reductive polymerization of divanillin in aqueous sodium hydroxide (route 15e).…”
Section: Lignin-derived Monomers To Biobased Polymers or Polymer Builmentioning
confidence: 87%
“… 367 These vanillin-derived diimines were converted into conjugated pyrrole-based polymers by a transformation exploiting a catechyl-substituted phosphonite-mediated multicomponent polymerization with commercial diacid chlorides and simple alkynes or alkenes (route 15d). 368 Importantly, this study reported, for the first time, a cross-conjugated polymer composed of both components of lignocellulosic biomass by using vanillin and furan-based acid chlorides. Polyvanillin, which is a functionalized polymer using totally renewable resources can be simply synthesized by electrochemical reductive polymerization of divanillin in aqueous sodium hydroxide (route 15e).…”
Section: Lignin-derived Monomers To Biobased Polymers or Polymer Builmentioning
confidence: 87%
“…8 The synthesis of benzoxazine from the same biosourced products was also demonstrated, where performance polymers with glass transition temperatures (T g ) above 300°C and thermal stabilities exceeding 440°C. 9 Other examples of biosourced monomers include various sugars used in polycondensations and ring opening polymerisations, 10,11 dihydrolevoglucosenone and syrinaldehyde that have been used as a precursor for methacrylic monomers and in subsequent free radical polymerisations, 12,13 vanillin in cross-conjugated pyrrole-based polymers as well as in electrochemical reductive polymerisation to realise polyvanillin, 14,15 furfurylamine, which has been used to modify magnolol to synthesize benzoxazine for use as a thermosetting resin through ring opening polymerisation, 9 alloocimene polymerised through a redox emulsion process, 16 as well as carene- 8 and pinene-derived lactams for anionic polymerisation of polyamides, 17 and phellandrene-derived polyols used in polyurethane foam synthesis. 18 Of the aforementioned monomer classes and species, terpenes and terpenoids are some of the most promising and most commonly used, with utility in fragrances and perfumes, food, cosmetics, pharmaceuticals and even cigarettes and other inhalation products.…”
Section: Introductionmentioning
confidence: 99%
“…S and G‐type lignin degradation fragments include small phenol compounds such as vanillin and syringic acid (SA). Many studies have focused on vanillin as platform chemical for synthesizing bio‐based aromatic polymers . Fache et al extensively reviewed different functionalization strategies to create different monomers for polycondenzation and radical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…studies have focused on vanillin as platform chemical for synthesizing bio-based aromatic polymers. [8][9][10][11][12][13][14] Fache et al extensively reviewed different functionalization strategies to create different monomers for polycondenzation and radical polymerization. The 22 monomers can then be used for the synthesis of bio-based polyester, polyurethanes, non-isocyanate polyurethanes (NIPU), and epoxy polymers.…”
mentioning
confidence: 99%